Chloro Fluro Carbon Gas Leak Monitoring System in Internet of Things-Based Air Conditioner - Muhammad Khafid Amrulloh; Indah Sulistiyowati (Universitas Muhammadiyah Sidoarjo, 2022)
Refrigerant leaks have a major impact on system operating performance, increasing power consumption, damage to components, and worse, global warming. This study aims to use a monitoring system based on the Internet of Things (IoT) to track Chloro Fluro Carbon gas in the air conditioning system. Using NodeMCU as a microcontroller-based control tool that has been assisted by a Wi-Fi module. The sensitivity level of refrigerant leakage is very high based on the sensitivity of the sensor used, namely MQ135. In experimenting, the refrigerant leak starts with the closest distance to the inaccessibility of the sensor readings to determine the acceleration of the sensor in detecting leaks. The voltage required for the MQ135 sensor is 5 Volt DC. This system uses an android application, namely blynk which has features for monitoring and warning users that the AC unit has detected a leak. The results of measuring the sensitivity level of the sensor are very high for alcohol, benzene, and NH3 gases. It can detect small leaks at a distance of 20 cm, at a moderate level of leakage it can detect further at 80 cm, and at a maximum detection level at a distance of 160 cm in closed rooms or low winds. Because the leakage distance is quite far, it will be affected by the wind, the sensor reading will be hampered because the refrigerant cannot hit the sensor.